Management of Immune thrombocytopenic purpura during pregnancy: A single center experience - Poudyal, B.S.; Sampurna, T.; Neupane, S.; Shrestha, P.R.; Chitrakar, N.; Pariyar, J.; Maharjan, K.K.; Mishra, Rupesh (Journal of Karnali Academy of Health Sciences, 2018)
Background: Immune thrombocytopenic Purpura (ITP) is the second most common cause of an isolated low platelet count during pregnancy. It account for about 3% of thrombocytopenic cases during delivery. Treatment is indicated, if there is an evidence of bleeding or platelet count is less than 30,000/µl. Herein, we presented a medical record of twenty-four pregnant women, who were diagnosed with ITP during pregnancy.Method: A total number of twenty four pregnant women diagnosed with primary ITP and having platelet count of less than 30000/µl were enrolled in the study. Oral prednisolone (1mg/kg) was started in all patients with an aim to keep the platelet count above 50000/µl during delivery. Steroid was continued for 21 consecutive days and were tapered (10 mg) every week, if platelet counts were above 30000/µl.Data pertaining to the ITP during pregnancy was recorded for age, platelet count, mode of delivery and complications related to steroid therapy and were analyzed by simple statistical analysis.Result: ITP was observed in about 58%, 25% and 17% of the cases during first, second and third trimester respectively. About, 63% of patients presented with purpuric rash, 18% presented with mucosal bleed, one present presented with hematuria and others were asymptomatic. More than two third of cases responded to the steroid and in those cases platelet counts were above 50,000/µl at the time of delivery. All subjects delivered a healthy child. There was no maternal mortality and post-partum hemorrhage was absent in all patients.Conclusion: Steroid is the treatment of choice for all cases of ITP. ITP is no longer a contraindication to the continuation of pregnancy, the tradition and tendency to advice for abortion in these pregnant mothers, may not be justifiable.